Proyecto de factibilidad para la creación de una empresa productora y comercializadora de carne de soya empacada al vacío en el cantón la Joya de los Sachas de la provincia de Orellana, para el año 2015 - Torres Balcázar, Alexandra Liliana (2016)
This project aims to create a producer and marketer of soy meat in Joya canton of Sachas Orellana province since this product is a legume of Chinese origin with great importance in the diet worldwide for its high content protein. Bineto (2014), states that "It is important because it contains substances that could affect the body. It is free of cholesterol and uric acid that cause digestive upset. It also has a 40% protein and B vitamins like thiamine and riboflavin." (p. 11). the protein contains high quality as meat, milk and eggs, with the advantage that is very low in saturated fat (common in meat) that are related to cardiovascular disease,this research aims to improve the nutrition of families sachences. In addition to the high consumption of soy can prevent osteoporosis and reduce symptoms of menopause because some products have great source of calcium. Given the problems described and as an incentive to the productive sector of the Canton Joya de los Sachas, to the use and processing of raw materials properly, it is undoubtedly an alternative enterprise technological innovation, to generate development. The aim of this research is to determine the feasibility of creating a producer and marketer of soy meat in Joya canton of Sachas Orellana province for which it was necessary to use different methods and techniques that research permits, as the deductive method, inductive method which part of the particular to reach general, the statistical method which consists of a series of procedures for handling qualitative and quantitative research data. The use of these methods allowed to reach the culmination of this work and that to achieve this had to follow in the footsteps of understanding and demonstration of the same application. Regarding a survey techniques were applied to 372 families in the province of Orellana and a survey of 279 owners of premises that sell soy meat. After conducting research the following results and conclusions were obtained: In the market study in the province of Orellana, a sample of 372 families; Weighted surveys have been analyzed and have been inferred results then perform market analysis, determining the potential for 114,010 pounds of soy meat demand, real demand 52,445 pounds of soy meat, effective demand for 49,298 pounds of meat soybeans, offering 16,262 pounds and unmet demand for 33,036 pounds. This information helps determine that the project can and should be run by the results obtained in the analysis of demand, supply and marketing levels for this product. The installed capacity of the project determines that the company will be able to produce 14,784 pounds of soy meat and whose capacity utilization will be 13,306 pounds of soy meat, which accounts for 90% of capacity utilization for the first year, and is determined the location of the same which will be located in the canton Joya de los Sachas, in the streets Panama and Bethlehem. Then engineering project is determining the production process which demands the use of suitable equipment, which will guarantee for a quality product and moderate prices, process diagrams, characteristics of operation and management, technical requirements as equipment, facilities, furniture and fixtures. Likewise an administrative study determined as a Limited Liability Company, and functional organizational structure to both legislative hierarchical levels, Executive Advisor, Auxiliary or support and operational level, as well as operating manuals, organizational charts was performed; which they serve as guidelines for implementing good organization, so there will be the following personnel: Manager, a secretary Contadora, a Caretaker-Guardian, who will be part of the administrative staff and operational staff distributed as follows: Two Workmen production and a seller. The project reaches an investment of $ 56,277.42 and will be financed with contributions from partners 55,58% of the total investment which corresponds to $ 31,277.42 and a loan that will keep the project with the Banco de Pichincha constitute the 44.42% corresponding to $ 25,000.00 to 10-year period at 15% annual interest. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 15,099.26, indicating that the project or investment is suitable. For this project, the IRR is 20.46% and this satisfactory value for the project, the time required to recover the original investment would be 5 years, 7 months and 8 days for this project, the sensitivity values are lower one therefore not affect changes in project costs and revenues increased 17.90% and decreased to 12.70%, respectively, ie the project is not sensitive to these changes. Subsequently the most significant conclusions and recommendations of the project is proposed.